Plant growth stage effects on the yield, feeding value and some morphological characters of the fiddleneck (Phacelia tanacetifolia Benth.) - Ates, Ertan; Coskuntuna, L.; Tekeli, A. S. (Cuban Journal of Agricultural Science, 2010)
The aim of this investigation was to determine the yield, some morphological characters and feeding values of fiddleneck (Phacelia tanacetifolia Benth.) at different growth stages (budding, half bloom and full-bloom). The experimental design was a randomized complete block with three replicates. The maximum plant height (106.33 cm) was measured for fiddleneck at full-bloom stage. The budding growth stage had highest leaf/stem ratio (0.60). The half bloom and full-bloom growth stages showed the highest green fodder yield (60.20 to 60.47 t ha-1) and dry matter yield (9.77 to 9.87 t ha-1). The budding growth stage showed higher value than other growth stages for CP (13.22%). The highest ADF ratio (37.33 %) was determined from plants at the full-bloom stage, whereas the maximum NDF (45.43-45.60 %) and ADL (22.43-23.70 %) ratios were found at the half bloom and full-bloom stages. There were no significant differences between the leaf length (19.76-20.11 cm), number of leaves per plant (27.65-30.21), main stem diameter (5.48-5.77 mm), Ca (0.97-0.98 %) and Mg (0.37-0.39 %) contents. Differences in P (0.42-0.67 %) and K (2.27-2.38 %) contents of the growth stages were significant. It is concluded that in the subtropical region under dry conditions, fiddleneck can be sown to obtain maximum green fodder yield, dry matter yield and mineral contents. Fiddleneck provided a balanced feed for animals throughout the growing season. Key words: fiddleneck, forage, growth stage, Phacelia tanacetifolia Benth., yield.